Russia in a Reconnecting Eurasia : Foreign Economic and Security Interests. - Safranchuk, Ivan (CSIS report., 2016)
Russia in a Reconnecting Eurasia examines the full scope of Russian national interests in the South Caucasus and Central Asia and analyzes the broad outlines of Russian engagement over the coming years. It is part of a six-part CSIS series, "Eurasia from the Outside In," which includes studies focusing on Turkey, the European Union, Iran, India, Russia, and China